An Exploration for a Holistic Approach to Upgrading Informal Settlements as an Alternative to Settlement Elimination: A case study on Okapale informal settlement, Windhoek - Uushona, Max (School of Architecture, Planning and Geomatics, 2025)
In 2019, Namibia's president declared informal settlements in Windhoek as a “Humanitarian crisis”, which he further declared to eradicate by 2025. The study highlighted a gap in the understanding of such a political statement's implications on the attitudes and efforts towards informal settlements upgrading processes. The study aim was therefore to unpack how the eradication declaration was interpreted, to assess its implications on the informal settlements upgrading practices in Windhoek, and to explore more nuanced and holistic means towards enhancing upgrading practices in Windhoek. The study problematizes the outdated eradication rhetoric used to enunciate informal settlements challenges. The study was necessitated to bridge the gap in understanding between political statements and their implications on planning discourses. The study methodology was qualitative- the case and critical discourse analysis methods were used. The critical discourse analysis traced the emergence of the eradication declaration, while the case method investigated the responsiveness and performance of the Municipality's upgrading strategy. A sample size of ten Thlabanelo1 households was selected, while seven Municipality officials and five participants from academia and NGO category participated. Semi-structured, focussed group interviews and field observations were employed as techniques. The study found the eradication declaration to conform to Mitlin's (2020) political settlements concept, which political elites use to generate rents. Participants ignored the rhetoric. They instead appreciated the government's interest on informal settlements. Furthermore, the participants leaned towards Andrews et al's (2012) 'isomorphic mimicry' concept in interpreting the president's declaration. The theoretical concepts 'conflicting rationalities' (Watson, 2003) and 'urban fantasies' (Watson, 2014) reinforced some findings, such as conflicting positionality on the 'upgrading' concept [and what it constitutes]; and the imposition of formal planning standards on the upgrading of informal contexts. The study also highlighted the need for the City to adopt co-production towards enhancing and fast-tracking upgrading. The critical preposition which emerged supports that political statements have engendering implications on informality and upgrading discourses, hence the need for institutions to collectively position themselves in national statements, to ensure equitable production and distribution of rents for all. The eradication declaration thus engendered dissected attitudes and rationalities towards informal settlements